Concentration of serum amyloid A in clinically normal endurance horses in Malaysia - Rajendren, Sujey Kumar; Khairuddin, Nurul Hayah; Sugnaseelan, Sumita (Veterinary Association Malaysia, 2019)
Endurance horses continuously undergoing training. This will cause inflammation which leads to acute phase reaction with the production of acute phase protein, especially serum amyloid A (SAA). The purpose of this study was to establish concentration of SAA in normal endurance horses in the blood serum using two-site enzyme linked immunoassay (ELISA) technique. Horse sera were aliquoted from blood taken from jugular venipuncture. The highest concentration of SAA was observed in horses rested between 12 months and 24 months. The lowest concentration of SAA was noticed in horses rested more than 24 months. All the horses between 6 and 11 years old have high SAA concentration. When resting intervals were compared against gender of the horses, it was noted that all mares have high SAA concentration compared to gelding and stallion. Whereas SAA concentration in Thoroughbred horses were high compared to Arabian horses in all rest intervals. The SAA concentration in horses rested more than 24 months was low most probably because the horses recovered well from the inflammatory process happened during the endurance race.